The role of block chain technology and Internet of Things (IoT) to protect financial transactions in crypto currency market. (2022) - Ahamad, Shahanawaj; Gupta, Priti; Bikash Acharjee, Purnendu; Padma Kiran, K.; Khan, Zarrarahmed; Faez Hasan, Mohammed
Abstract: The most well-known cryptocurrency, Bitcoin, is the one for which blockchain technology was created. A cryptocurrency is a digital means of exchange that uses encryption techniques to manage the creation of monetary units and verify the transfer of funds. A blockchain is a decentralised ledger that records all peer-to-peer transactions. Blockchain is also recognised as the protocol of trust. This security concept uses decentralisation to establish a global index of all financial transactions that occur in a distinct network and makes them absolute. Blockchain technology establishes trust and harmony in direct communication between two parties without the involvement of a third party. Participants can confirm transactions without the requirement for a central clearing authority using this technology. Third-party trusted intermediaries have a character for triggering transaction delays. There would be speedier reconciliation between transacting parties and participants if such intermediaries were not present. In addition, the Internet of Things is a new technology that allows virtual and physical items to link and communicate with one another, resulting in the creation of new digitised services. When the number of devices connected through an IoT network grows. However, this data is not encrypted; it does not provide privacy. In this regard, blockchain technology might give massive benefits because it can quickly secure the anonymity of the obtained data. Furthermore, Blockchain can assist in solving most of the security vulnerabilities and traceability concerns in financial transactions by keeping track of how devices interact. In this state, they are, and how they transact with other IoT devices. A blockchain is hack-resistant and has a low danger of being hacked to improve data security. This article aims to explain the structure and operation of Blockchain and IoT in the context of securing financial transactions in the cryptocurrency market.